Influência do alto teor de Mo na microestrutura de ligas Fe-Cr - Reis, Francisco Evaristo Uchôa (2007)
The effects of aging at 400oC and 475oC the corrosion resistance, the mechanical and magnetic properties of three kinds of ferritic steels with high molybdenum content were investigated. The hardening caused by the presence of phase α 'after exposure at both temperatures was measured, and was observed which is more intense at 475 ° C. The susceptibility to localized corrosion increased with aging time at two temperatures, also be more significant at 475 ° C to 400 ° C. Compared to stainless steel AISI 444, these steels with high content of molybdenum, showed greater resistance to corrosion. The effects in the Mössbauer spectra were also analyzed.